2019
DOI: 10.3390/metabo9120291
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Metabolomic Profiling and Pathway Analysis Reveal the Metabolic Signature of Ulcerative Colitis

Abstract: The onset of ulcerative colitis (UC) is characterized by a dysregulated mucosal immune response triggered by several genetic and environmental factors in the context of host–microbe interaction. This complexity makes UC ideal for metabolomic studies to unravel the disease pathobiology and to improve the patient stratification strategies. This study aims to explore the mucosal metabolomic profile in UC patients, and to define the UC metabolic signature. Treatment- naïve UC patients (n = 18), UC patients in deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…These phenotypic findings have also been observed with MSbased lipidomic [21] (i.e., a subset of the metabolome) and metabonomic studies [20] and may discriminate between patients with flares of UC, patients with quiescent UC, and control individuals in multivariate modeling. Here 220 different lipids and 177 metabolites were identified, respectively, but the highest significant variation was observed within the sphingolipids, phosphatidylcholine (PC), lysophosphatidylcholine (LPC), and a range of amino acids.…”
Section: Metabonomic Remission and Quiescent Diseasesupporting
confidence: 52%
“…These phenotypic findings have also been observed with MSbased lipidomic [21] (i.e., a subset of the metabolome) and metabonomic studies [20] and may discriminate between patients with flares of UC, patients with quiescent UC, and control individuals in multivariate modeling. Here 220 different lipids and 177 metabolites were identified, respectively, but the highest significant variation was observed within the sphingolipids, phosphatidylcholine (PC), lysophosphatidylcholine (LPC), and a range of amino acids.…”
Section: Metabonomic Remission and Quiescent Diseasesupporting
confidence: 52%
“…Further, UC patients with mild to severe disease activity have been shown to express low levels of genes involved in butyrate uptake and oxidation [ 36 ]. Also, a recent pathway enrichment analysis showed altered butyrate metabolism in UC patients [ 37 ], and our group demonstrated that butyrate more potently down-regulates gene expression of inflammatory pathways in non-inflamed controls than in inflamed tissue of UC patients [ 38 ]. It should be noted that the effect of butyrate may differ according to the local microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The GC-MS analysis was performed with Agilent 6890 GC equipment and a fused silica capillary column (10 m × 0.18 mm I.D.) with a chemically bonded 0.18 µm DB5-MS stationary phase (J&W Scientific, Folsom, CA, USA) as previously described [ 38 ].…”
Section: Methodsmentioning
confidence: 99%